Percepção ambiental e o manejo da paisagem por diferentes comunidades indígenas e rurais da Amazônia maranhense - Loch, Vivian do Carmo (2020)
Human actions play an important role in the transformation of natural landscapes. The ecological, economic, and social consequences of these transformations, despite being the object of study by many researchers, still do not receive due attention from society in general and our representatives, mainly with regard to the reduction of deforestation, the predatory use of forests, loss biodiversity, soil degradation, reduction of reservoirs and water sources and increase in global temperature. While we are experiencing an environmental crisis, some authors claim that our environmental crisis is a cultural crisis. As such, it cannot be resolved by scientific, technological, political, and economic means alone. In the state of Maranhão, we find different human groups interacting with nature according to their beliefs, cultures, and needs (indigenous, descendants of quilombos, babassu coconut breakers, artisanal fishermen, traditional farmers, etc.). Some groups, apparently, develop more harmonious bonds with nature than others and can serve as inspiration in the ecological restoration process. Thus, this research sought to understand how different communities living in the Amazon region of Maranhão perceive, interact, and manage nature. And how this interaction changes the landscape, leading to ecological degradation, conservation, and/or restoration. Three communities were selected that manage the natural landscape in different ways: quilombolas relocated from Agrovilas de Alcântara; Indigenous people from Aldeia Awa (Indigenous Land Caru) and farmers from Vila Bom Jesus (settlers of the Amazon Settlement Project). To better understand the relationship of communities with natural resources and how their use and management recreate and modify the landscape, several participatory tools were used, such as: participant observation, semi-structured interviews, guided tours, free lists, and checklists. To understand the conservation level of the three studied areas, we analyzed land cover changes across 3 decades (from 1985 to 2017) in a 3.5 km buffer area from the center of each community. From the triangulation of the data obtained by these methods, we present a list of forest species of biocultural value for the three communities, obtained from the local perception of species of ecological importance and utility value, which can contribute to the biocultural restoration of the Amazon Maranhão from an intercultural perspective; we present an analysis of the intangible values of forest species in this biome based on the Awa cosmology, reflecting on the importance of preserving the memory of these people; finally, we seek to identify factors that influence individuals to adopt diversification practices in their agroecosystems with a focus on planting trees (the techniques understood were agroforestry systems, productive backyards, and conservation of permanent protection areas) seeking to scale agroecological transition processes and increased resilience of environments based on forest biodiversity. With this, we bring important elements to sensitize ecologists, environmentalists, government officials, and society in general, to a look at nature that encompasses tangible and intangible cultural dimensions, to promote greater inclusion in the governance of natural environments.